"Community Without Propinquity" - Teaching Legal History Intercontinentally - Douglas Harris; John McLaren; W Wesley Pue; Simon Bronitt (Legal Education Review)
The 1998 Federal budget included an allocation of $1.74 million over four years (1998/99 to 2002/2003) for “[d]eveloping more and better Clinical Legal Education to maximise service delivery to disadvantaged clients and cooperation with universities”. This is a significant development for Australia’s small clinical legal education (CLE) movement which, with only one exception, had not previously received direct Federal funding. While this provision of funding is obviously welcomed, the Commonwealth government’s objectives for this funding appear to focus on community service rather than educational outcomes. The Commonwealth is clearly of the view that CLE has potential as a vehicle for the provision of inexpensive legal advice.